Modulation of Enzyme Activity in the Kynurenine Pathway by Kynurenine Monooxygenase Inhibition - Phillips, Robert S.; Iradukunda, Emma Carine; Hughes, Tamera; Bowen, J. Phillip (Frontiers in Molecular Biosciences, 2019)
The kynurenine pathway is the major route for tryptophan metabolism in mammals. Several of the metabolites in the kynurenine pathway, however, are potentially toxic, particularly 3-hydroxykynurenine, 3-hydroxyanthranilic acid, and quinolinic acid. Quinolinic acid (QUIN) is an excitotoxic agonist at the NMDA receptor, and has been shown to be elevated in neurodegenerative diseases such as Alzheimer’s Disease and Huntington’s Disease. Thus, inhibitors of enzymes in the kynurenine pathway may be valuable to treat these diseases. Kynurenine monooxygenase (KMO) is the ideal target for an inhibitor, since inhibition of it would be expected to decrease the toxic metabolites and increase kynurenic acid (KynA), which is neuroprotective. The first generation of KMO inhibitors was based on structural analogues of the substrate, L-kynurenine. These compounds showed reduction of QUIN and increased KynA in vivo in rats. After the determination of the x-ray crystal structure of yeast KMO, inhibitor design has been facilitated. Benzisoxazoles with sub-nM binding to KMO have been developed recently. Some KMO ligands promote the reaction of NADPH with O2 without hydroxylation, resulting in uncoupled formation of H2O2. This potentially toxic side reaction should be avoided in the design of drugs targeting the kynurenine pathway for treatment of neurodegenerative disorders.